The Effect of Financial Strength on Firm Value with Financial Performance as an Intervening Variable - Utama, Oktavian Arga Dwi; Uzliawati, Lia; Astuti, Kurniasih Dwi (Accounting Department, 2025)
Purpose — This research aims to test and analyze the effect of financial strength on firm value with financial performance as an intervening variable. Design/methodology/approach — The population in this study is banking companies listed on the Indonesia Stock Exchange (IDX) for 2018-2023. The purposive sampling technique to obtain a sample resulted in 240 observations. The analysis technique used is multiple linear regression processed with STATA software and path analysis with the help of an online Sobel calculator. Findings—The results of the hypothesis testing indicate that capital and asset quality do not significantly impact financial performance. Conversely, managerial efficiency hurts financial performance. Moreover, capital, managerial efficiency, and financial performance positively affect firm value, while asset quality hurts firm value. Meanwhile, financial performance is not an intervening variable in the relationship between financial strength and firm value. Practical implications—This research indicates that management should prioritize enhancing the firm’s capital and asset quality, as these factors significantly influence firm value. By increasing capital accessibility and engaging in selective lending processes, management can boost firm value. Investors may wish to closely monitor banking financial ratios, particularly those related to capital availability, credit provision efforts, and banking efficiency, to make informed investment decisions. Originality/value — This research started from the observation that many existing studies show inconsistent results and diversity in indicators. Therefore, this study combines indicators used to measure financial strength variables: capital, asset quality, and managerial efficiency. The indicator used for the firm value variable is Price to Book Value (PBV), while the financial performance variable is measured using Return on Assets (ROA). The difference between this study and previous research lies in its use of financial performance as an intervening variable, its concentration on the banking sector in Indonesia, and the research period of 2018-2023. Paper type — Quantitative